Two-dimensional parametric mapping and characterization of semiconductor devices using optical-feedback confocal microscopy - Sarmiento, Raymund Lee Antonio C. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
A method of measuring very important two-dimensional parameters of semiconductor devices is demonstrated using an optical feedback confocal microscope. By utilizing different wavelength laser diodes for the microscope, either photothermal stimulation or photoexcitationn of the semiconducting samples is achieved. In both cases, simultaneous acquisition of reflectance and current images permits a comprehensive characterization of relatively large area semiconductor devices at diffraction-limited resolution.